State-Building/State-Destroying in Ethiopia – A Backdrop to the Tigray Genocide - Abbay, Alemseged (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
Federalist Tigray and unitarian Amhara have been historical rivals in the daunting task of state-building in Ethiopia. To neutralize Tigray and its de facto federalism (1872–89), Amhara found a formidable ally in Italy, which colluded with Britain to have “a place in the sun.” Amhara rewarded Italy with half of Tigray, which was christened “Eritrea,” and imposed the unitarian system in the country. Worse still, in the middle of the 1950s, Amhara annexed the western and southern parts of Tigray. Tigray and Eritrea (which returned to Ethiopia in 1952) were suffocated by amharanization and political centralization, the twin pillars of the unitarian system. Military insurgencies brought the system to an end in 1991 and the Tigrayans who assumed the reins of power introduced de jure federalism, to the chagrin of the Amhara. The paper offers a critical historical analysis of state-building and state-destroying in Ethiopia, with particular attention given to the Amhara return to power in 2018 and humanity’s newest genocide in Tigray.